Renin Angiotensin System and Cardiovascular Disease - DeMello, Walmor C.; Frohlich, Edward D.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2010)
The renin angiotensin system plays an essential role on cardiac and vascular functions and their connection in the generation of cardiovascular diseases. Renin Angiotensin System and Cardiovascular Disease covers indispensable aspects such as intracellular signaling, regulation of cell volume in the failing heart, the presence of an intracrine renin angiotensin system, and the influence of prorenin/renin, angiotensin II, angiotensin (1-7) and aldosterone. Furthermore, the role of the mineralocorticoid receptor as an imperative component of the intracrine renin angiotensin system and as a regulator of extracellular action of angiotensin II is described, reinforcing the view that aldosterone inhibitors are helpful in the treatment of heart failure and hypertension. Renin Angiotensin System and Cardiovascular Disease provides readers with an outstanding review of the major topics involving the renin angiotensin system and cardiovascular disease. With contributions by an international panel of experts, Renin Angiotensin System and Cardiovascular Disease presents the most relevant aspects of the role of the renin angiotensin aldosterone system on cardiovascular diseases including hypertension, congestive heart failure, atherosclerosis and diabetes. The volume Editors, Dr. Walmor C. DeMello and Dr. Edward Frohlich, both established specialists in their respective fields, team up to discuss a range of topics from Renin Angiotensin Aldosterone System and Pathobiology of Hypertension to Inhibiting the Renin Angiotensin Aldosterone System in Patients with Heart Failure and Myocardial Infarction.
Systemic Versus Local Renin Angiotensin Systems. An Overview -- Clinical Import of the Local Renin Angiotensin Aldosterone Systems -- Renin, Prorenin, and the (Pro)Renin Receptor -- Local Renin Angiotensin Systems in the Cardiovascular System -- Renin-Angiotensin-Aldosterone System and Pathobiology of Hypertension -- AT1 Receptors, Angiotensin Receptor Blockade, and Clinical Hypertensive Disease -- Structural and Electrophysiological Remodeling of the Failing Heart -- Inhibiting the Renin Angiotensin Aldosterone System in Patients with Heart Failure and Myocardial Infarction -- Left Ventricular Hypertrophy and Treatment with Renin Angiotensin System Inhibition -- Angiotensin-(1-7), Angiotensin-Converting Enzyme 2, and New Components of the Renin Angiotensin System -- Kinin Receptors and ACE Inhibitors: An Interrelationship -- Kinins and Cardiovascular Disease -- CMS and Type 2 Diabetes Mellitus: Bound Together by the Renin Angiotensin Aldosterone System -- Renin Angiotensin Aldosterone System and Cardiovascular Disease -- Renin Angiotensin System and Atherosclerosis -- Renin Angiotensin System and Aging.
Keywords: Medicine; Internal medicine; Angiography; Cardiology; Medicine & Public Health; Cardiology; Angiology; Internal Medicine